PREPARATION OF FUTURE TEACHERS OF MUSIC ART FOR INSTRUMENTAL PERFORMANCE - Shcherbak, Ihor (International Journal of Innovative Technologies in Social Science, 2020)
The article reviews the concept of instrumental performance training for prospective music teacher through the prism of system approach. It is considered to be psychological and educational issue in terms of the tasks for instrumental performance practice of specialists in comprehensive school. The author points out that the implementation of all kinds of instrumental performance practice of prospective music teacher should be found on the fusion of instrumental performance, psychological and pedagogical skills, sophisticated aesthetic taste and conscious respect to music. The author of the article believes that the intention to equip students with profound book learning and methodological knowledge in the domain of instrumental performance practice should be pursued through the development of their intellectual abilities, formation of genre and stylistic notion, faculty to make sense of musical forms and art expressive means. Improving the quality of professional training of future music teachers, in particular the improvement of their instrumental and performing skills is one of the leading tasks of modern music and pedagogical education.